2014
DOI: 10.1016/j.jpain.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Cytokine Gene Variations and Severe Persistent Breast Pain in Women Following Breast Cancer Surgery

Abstract: Persistent pain following breast cancer surgery is a significant clinical problem. While immune mechanisms may play a role in the development and maintenance of persistent pain, few studies have evaluated for associations between persistent breast pain following breast cancer surgery and variations in cytokine genes. In this study, associations between previously identified extreme persistent breast pain phenotypes (i.e., no pain versus severe pain) and single nucleotide polymorphisms (SNPs) spanning 15 cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 74 publications
(86 reference statements)
4
41
0
1
Order By: Relevance
“…Research on persistent pain in breast cancer revealed that the variation of rs11674595 was correlated with severe pain, which could be conducive to the prognosis analysis of breast cancer. 38 In combination with the results obtained in the present study, susceptibility to disease or syndromes could be ascribed to the dysregulation of IL1R2 resulting from the polymorphic SNPs (rs2072472 and rs11674595).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Research on persistent pain in breast cancer revealed that the variation of rs11674595 was correlated with severe pain, which could be conducive to the prognosis analysis of breast cancer. 38 In combination with the results obtained in the present study, susceptibility to disease or syndromes could be ascribed to the dysregulation of IL1R2 resulting from the polymorphic SNPs (rs2072472 and rs11674595).…”
Section: Discussionsupporting
confidence: 82%
“…Rs2072472 has been demonstrated in ankylosing spondylitis and endometriosis for Northern Chinese Han and Korean women, respectively whereas no significant associations were observed with respect to the risk of disease. Research on persistent pain in breast cancer revealed that the variation of rs11674595 was correlated with severe pain, which could be conducive to the prognosis analysis of breast cancer . In combination with the results obtained in the present study, susceptibility to disease or syndromes could be ascribed to the dysregulation of IL1R2 resulting from the polymorphic SNPs (rs2072472 and rs11674595).…”
Section: Discussionsupporting
confidence: 74%
“…Supporting this, a separate study in the same cohort concluded that persistent breast pain is associated with genetic variation in inflammatory cytokines/receptors such as IL-1R and IL-10. 27 Together, these data raise the possibility of unidentified interactions between these inflammatory components and K 1 (or other ion) channels to establish a hyperexcitable phenotype, circumstantial evidence of which is already found in the literature. 5,8,28 Since analysis was limited to a small selection of genes, it would be informative to interrogate the involvement of additional K 1 channels, such as Kv7 channels that are known to be directly modulated by inflammatory agents.…”
mentioning
confidence: 59%
“…A similar study conducted among breast cancer women following surgery (postoperatively) [118] demonstrated that carriers of IL1R2 (rs11674595) had higher odds of developing a severe persistent breast pain while those harbouring the IL10 haplotype A8 (made up of seven SNPs i.e. rs3024505, rs3024498, rs3024496, rs1878672, rs1518111, rs1518110, rs3024491) had decreased odds of having severe persistent breast pain.…”
Section: Genetic Polymorphisms Associated With Common Symptoms Experimentioning
confidence: 85%